The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2004
DOI: 10.1111/j.1582-4934.2004.tb00326.x
|View full text |Cite
|
Sign up to set email alerts
|

The ultrastructural aspects of neoplastic myoepithelial cell in pleomorphic adenomas of salivary glands

Abstract: The salivary gland pleomorphic adenoma is a benign epithelial neoplasm, histologically characterized by a great diversity of morphological aspects. According to literature data, the pleomorphic adenoma represents 45-74 % of all the salivary gland tumors [1][2][3][4]. At the Armed Forces Institute of Pathology (AFIP) the pleomorphic adenomas represent 60 % of the benign tumors from all the salivary gland sites: 61 % of the major gland tumors and 54 % of the minor gland tumors [5]. AbstractThe purpose of this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 49 publications
(51 reference statements)
0
10
0
1
Order By: Relevance
“…PA is characterized by great histologic diversity; however, PA with exuberant squamous metaplasia is uncommon and can be diagnostically challenging [1][2][3]9]. Focal squamous metaplasia in PA can be related to ischemia [16], and may be found in about 25% of the PA [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PA is characterized by great histologic diversity; however, PA with exuberant squamous metaplasia is uncommon and can be diagnostically challenging [1][2][3]9]. Focal squamous metaplasia in PA can be related to ischemia [16], and may be found in about 25% of the PA [8].…”
Section: Discussionmentioning
confidence: 99%
“…Histological diversity is the hallmark of pleomorphic adenoma (PA). Its histological patterns may vary considerably among different parts of the same tumor [1]. Not only does the proportion between epithelial and chondromyxoid stroma vary, but some metaplastic variations also occur in the epithelial and stromal components.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that salivary gland tumors consist of several tumor cell components, such as myoepithelial-like tumor cells, duct-like tumor cells, acinus-like tumor cells, epidermoid-like tumor cells, mucin-producing tumor cells and tumor cells with mesenchymal differentiation (17). There are several reports concerning the direction of differentiation in salivary gland tumors or the tumor stem cells of salivary gland tumors (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). Sato et al established a cultured salivary gland tumor cell line, HSG (21) and investigated the differentiation potentials of HSG cells (22)(23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…It was concluded that the HSG cells or transformed intercalated duct cells might be the tumor stem cells for several components of the salivary gland tumors. On the other hand, under the basis of the observation of histopathology of salivary gland tumors, Aigner et al (27) and several other pathologists (28)(29)(30)(31)(32)(33) reported that myoepithelial-like tumor cells might be the tumor stem cells or procurer cells for several components in salivary gland tumors (22)(23)(24)(25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…1 Salivary gland PAs show great histologic variation and present 2 major proliferating cellular types: luminal and abluminal cells (with myoepithelial cell morphology). 2 Molecular heterogeneity in these tumors has also been proved. 3 PAs can recur or undergo malignant transformation, 4,5 and the clarification of their molecular pathogenesis may help improve the understanding of such phenomena.…”
mentioning
confidence: 99%